ASSESMENT OF INTERNAL SERVICE QUALITY DIMENSIONS USING THE TOPSIS METHOD TO IMPROVE SERVICE QUALITY AT THE OUTPATIENT REGISTRATION SITES AISYIYAH SITI FATIMAH TULANGAN HOSPITAL - Siti Aisyah Lutfiyah; Resta Dwi Yuliani (Antis Publisher, 2025)
Objective: The aim of this research is to find a solution for each alternative by using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method as a basis for measuring the quality of health services at the Aisyiyah Siti Fatimah Tulangan Hospital, where there are still problems with service quality and patient satisfaction due to the lack of supporting facilities in the registration waiting room. Method: This research uses descriptive quantitative methods with a population consisting of patients undergoing new and existing outpatient treatment at the Aisyiyah Siti Fatimah Tulangan Hospital, and the sample size determined using the Slovin formula resulted in 98 respondents. Result: The results of this research obtained an average tangibles score of 52.80%, reliability 64.06%, responsiveness 78.00%, empathy 64.33%, competence 76.84%, communication 78.00%, and access 65.39%; overall it is categorized as satisfied, although the tangibles dimension indicates remaining obstacles. Novelty: The study provides practical recommendations for additional supporting facilities in the waiting room to improve patient comfort and satisfaction, offering a focused approach to enhancing the tangible dimension of healthcare service quality.